The Development of Ijma': The Practices of the Khulafa 'al Rashidun and the Views of the Classical Fuqaha' (American Journal of Islam and Society, 1992)
In the beginning, ijma' (consensus) was more a pragmatic necessity thanan explicit Shari'ah principle. It was first applied to public policy considerationsand was used to settle some crucial questions that had arisen (we will discussthe issue of khilafah separately, where we can see how the Companions attemptedto settle this issue). The event of the Thaqifah of Banu Sa'idah was a great testfor the ummah's social order and alerted the leaders to potential future crises.The Companions therefore gave immediate attention to the succession issue,and sincere people realized that the ummah needed a sociopolitical doctrine thatwould support its desired sociopolitical development and keep it united. Amongthe khulafa 'al rashidun, particularly Abu Bakr and ' Umar, great emphasis wasplaced on the principle of shura, which was, in fact, a means to realize ijma '.The development of ijma ' was an opportune and proper approach to preservethe ummah's unity and integrity. As the Companions were greatly concernedabout the establishment of the khilafah by means of ijma', 'Umar rejected allattempts to use other methods.'Although the fuqaha' (jurists) refer to the Qur'anic ayat and the ahadith asa normative basis for ijma', precedents are found in the practice the khulafa 'al rashidun and the Companions, who made agreed-upon decisions in manysocial and religious matters. The jurists are unanimous in agreeing that theCompanions' ijma' is a complete and definite source of law, and some recognizeit to the exclusion of all other source. The classical jurist al Khatib al Baghdadi ...